FLOOD INUNDATION MODELING FOR KOTA TINGGI CATCHMENT BY COMBINATION OF 2D HYDRODYNAMIC MODEL AND FLOOD MAPPING APPROACH - M. R. M. Adib; M. B. Saifullizan; T. Wardah; D. Rokiah; A. Junaidah (Lowland Technology International, 2011)
Flood inundation model in lowland catchment area plays an important role in flood management. This paper describes the development of flood inundation model where Kota Tinggi catchment has been chosen as the case study. This model is built using InfoWorks River Simulation (RS) and it is combined with flood mapping techniques. This model is calibrated using historical flood event on 12th January 2007. It is found that the water level of the river overflows due to heavy rainfall on January 12th 2007, and the highest rainfall data of 50.8mm was recorded. The outflow hydrograph from the breach was estimated to perform inundation simulation. Flood inundation simulation shows that the water spread out through the Kota Tinggi catchment and the maximum inundation depth was above 10 m. The results of this research will benefit future modeling efforts by providing a tool for hydrological forecasts of flooding on lowland areas. While designed for the Kota Tinggi catchment, this model may be used as a prototype for model applications in other areas of the country.